1995
DOI: 10.1016/0735-1097(95)00394-0
|View full text |Cite
|
Sign up to set email alerts
|

Valve strands are strongly associated with systemic embolization: A transesophageal echocardiographic study

Abstract: Valvular strands visualized by transesophageal echocardiography are associated with systemic embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
2
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 11 publications
2
64
2
2
Order By: Relevance
“…Freedberg, et al suggested that our patient's lesions could have been Lambl's excrescences, which are seen on pathologic examination of the valve strands to be highly mobile, fine, threadlike excrescences less than 1 mm in width. 5) Distinguishing between PFE and giant Lambl's excrescences is very difficult on echocardiography. The former may have a more sessile or broader stalk than the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freedberg, et al suggested that our patient's lesions could have been Lambl's excrescences, which are seen on pathologic examination of the valve strands to be highly mobile, fine, threadlike excrescences less than 1 mm in width. 5) Distinguishing between PFE and giant Lambl's excrescences is very difficult on echocardiography. The former may have a more sessile or broader stalk than the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography revealed an L-R shunt toward the pulmonary trunk, severe pulmonary regurgitation, and severe tricuspid regurgitation, however detected no intracardiac mass. Cardiac catheterization revealed a pulmonary/systemic flow ratio of 2.5, pulmonary artery systolic pressure of 83 mm Hg, mean pulmonary artery pressure of 53 mm Hg, pulmonary capillary wedge pressure of 23 mm Hg, and pulmonary artery resistance of 984 dynes ⋅ sec/cm 5 . No significant coronary stenosis was observed by coronary angiography.…”
Section: Simultaneous Surgery For Patent Ductus Arteriosus Associatedmentioning
confidence: 99%
“…In a retrospective analysis, valvular strands on native and prosthetic valves were found in 5.5% of patients referred to TEE [4] and in 0.94% of patients aged 61-70 referred to both TTE and TEE [5]; as most of the patients who undergo TEE have a suspect of endocarditis or of a potential cardiac source of embolism, there could be a bias of selection, which makes differential diagnosis more challenging. That is the case of our patient, which is paradigmatic, as she was referred to TEE for suspect vegetation on the aortic valve; in this case a good clue of its real nature was the echocardiographic features of the finding, which was thin, highly mobile, regularly shaped and attached on the ventricular side of an otherwise normal aortic valve.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports strands account for a higher risk of stroke or embolism [4], but there is consensus in a conservative strategy of follow up for silent, asymptomat- ic lesions accidentally discovered. In our case, despite the patient was asymptomatic for prior cerebrovascular events, antiplatelet therapy was chosen, given the fact that she was considered at higher risk for her previous history of myocarditis and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, valvular strands were reported in 6.3 to 22.5% of stroke patients compared with 0.3 to 12% of control subjects. 7,8 A thrombotic or fibrotic origin was suggested by the development of valvular strands during thrombolytic therapy for a mitral valvular thrombus. 9 However, the finding that valvular strands are associated with ischemic stroke does not necessarily mean that they are the active embolic source.…”
Section: Discussionmentioning
confidence: 99%